Increased interbrain synchronization and neural efficiency of the frontal cortex to enhance human coordinative behavior: A combined hyper-tES and fNIRS study - Hongliang Lu; Xinlu Wang; Yajuan Zhang; Peng Huang; Chen Xing; Mingming Zhang; Xia Zhu (NeuroImage, 2023)
Coordination is crucial for individuals to achieve common goals; however, the causal relationship between coordination behavior and neural activity has not yet been explored. Interbrain synchronization (IBS) and neural efficiency in cortical areas associated with the mirror neuron system (MNS) are considered two potential brain mechanisms. In the present study, we attempted to clarify how the two mechanisms facilitate coordination using hypertranscranial electrical stimulation (hyper-tES). A total of 124 healthy young adults were randomly divided into three groups (the hyper-tACS, hyper-tDCS and sham groups) and underwent modulation of the right inferior frontal gyrus (IFG) during functional near-infrared spectroscopy (fNIRS). Increased IBS of the PFC or neural efficiency of the right IFG (related to the MNS) was accompanied by greater coordination behavior; IBS had longer-lasting effects on behavior. Our findings highlight the importance of IBS and neural efficiency of the frontal cortex for coordination and suggest potential interventions to improve coordination in different temporal windows.